Method for improving mechanical property and corrosion resistance of erbium-containing Al-Mg alloy
Through pre-deformation, stabilization annealing and anodizing treatment methods, the problem of corrosion resistance of Al-Mg alloy decreases when the magnesium content is greater than 3.5 wt.%, and the dual improvement of the mechanical properties and corrosion resistance of the alloy is achieved.
Patent Information
- Application Number
- CN202510122120.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-24
AI Technical Summary
When the magnesium content of the existing Al-Mg alloy is greater than 3.5 wt.%, the corrosion resistance is reduced, and it is difficult to improve its mechanical properties and corrosion resistance at the same time.
The treatment method of combining pre-deformation, stabilization annealing and anodizing is adopted to increase the dislocation density inside the alloy by compounding the addition of Er and Zr elements, so that the Al-Mg-Zn phase can replace the β phase, and the corrosion resistance is further improved through the anodizing treatment.
It significantly improves the mechanical properties and corrosion resistance of the new erbium-containing Al-Mg alloy and extends the service life of the material.
Smart Images

Figure HDA0005259133100000011 
Figure HDA0005259133100000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nonferrous metals, and in particular relates to a method for improving the mechanical properties and corrosion resistance of a novel erbium-containing Al-Mg alloy. Background Art
[0002] Aluminum-magnesium alloys are widely used in structural parts in the fields of housing construction, automobile manufacturing, aerospace and shipbuilding due to their low density, excellent corrosion resistance, good processing weldability and high specific strength. In particular, their application as structural parts in corrosive marine environments is particularly prominent. Al-Mg alloys have medium strength. Since the main alloying element Mg cannot be dispersed and precipitated, they are non-heat-treatable aluminum alloys. The main strengthening methods are solid solution strengthening and deformation strengthening of Mg. Due to the addition of magnesium, the overall strengthening effect in the alloy is significantly enhanced. The addition of magnesium is beneficial to the strengthening of Al-Mg alloys for two main reasons: (1) The addition of magnesium effectively reduces the steady-state grain size and increases the dislocation density and dislocation storage capacity; (2) Magnesium atoms tend to segregate to grain boundaries during plastic deformation, thereby reducing the mobility of grain boundaries and increasing the defect density of grain boundaries. At the same time, some reports show that adding a small amount of rare earth elements (such as Sc, Zr, Er, etc.) to Al alloys can generate nano-sized second phase particles in the Al matrix, which are coherent and dispersed with the Al matrix, and have a significant improvement on the mechanical properties of aluminum alloys. Since 5xxx aluminum alloys are widely used in corrosive environments such as the ocean, in addition to their mechanical properties, resistance to intergranular corrosion (IGC) is also very important. When the magnesium content in the Al-Mg alloy is greater than 3.5wt.%, magnesium atoms diffuse preferentially from α-Al to form β-Al3Mg2 phases along the grain boundaries, which seriously reduces the corrosion resistance of the Al-Mg alloy. The generation of IGC in 5xxx aluminum alloys is related to the continuity of the β phase at the grain boundaries. The alloying element zinc has a certain influence on the mechanical properties, intergranular corrosion behavior and microstructure of Al-Mg alloys. In Al-Mg alloys, the stable Al-Mg-Zn ternary phase precipitates uniformly inside the grains and can heterogeneously nucleate at dislocations and Al-Mn phase boundaries, inhibiting the segregation of Mg atoms to the grain boundaries, resulting in discontinuous precipitation of T phase at the grain boundaries, which significantly reduces the corrosion sensitivity of Al-Mg-Zn alloys and improves the strength of the alloy.
[0003] The present invention adopts a new aluminum-magnesium alloy, and Er and Zr elements are added to the aluminum-magnesium alloy in a composite manner, so that the alloy has a certain precipitation strengthening effect compared with the traditional Al-Mg alloy. After that, the alloy is pre-deformed to a certain extent. The pre-deformation can increase the dislocation density inside the alloy, which has a great contribution to the dislocation strengthening mechanism of the alloy, thereby improving the mechanical properties of the alloy. The stabilization annealing process carried out after the pre-deformation can promote the Al-Mg-Zn phase to replace the β phase continuously precipitated at the grain boundary, thereby improving the corrosion resistance of the alloy. The last anodizing treatment process can remove the surface oxide film and impurities, and further improve the corrosion resistance of the alloy. Thereby achieving a dual improvement in the strength and corrosion resistance of the new erbium-containing Al-Mg alloy, greatly improving the service life of the material. Summary of the invention
[0004] The main purpose of the present invention is to provide a treatment method combining pre-deformation, stabilization annealing and anodizing to solve the contradiction between the strength and corrosion resistance of the novel erbium-containing Al-Mg alloy, so as to expand the application range of the actual production process.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] Step 1: Preparation of Al-Mg alloy sheet
[0007] The aluminum alloy used in the present invention has a chemical composition (wt.%) of 5.2-6.2% Mg, 0.3-0.8% Zn, 0.5-0.7% Mn, 0.04-0.3% Er, 0.05-0.15% Zr, Fe<0.3%, Si<0.2%, and the rest is Al; the aluminum-magnesium alloy sheet is prepared by semi-solid forming technology; the first step is to melt the mixture at 600-700°C; the second step is to quickly cool the alloy to a semi-solid state at 480-580°C; the third step is to : Use a spiral stirrer to stir the semi-solid aluminum-magnesium alloy at a stirring speed of 300-500 rpm for 10-30 minutes; Step 4: Perform a double-stage homogenization annealing of the alloy at (415-425)°C×360min+(515-525)°C×1000min; Step 5: Heat the alloy to 500°C and keep it warm for 16 hours before extruding, with an extrusion pressure of 103mN, an extrusion speed of 0.6mm / s, and an extrusion ratio of 26.57, to finally obtain a new erbium-containing aluminum-magnesium alloy hot extrusion sheet;
[0008] Step 2: Preparation of pre-deformed samples
[0009] The pre-deformation method is a combination of cold rolling and cold drawing; the erbium-containing aluminum-magnesium alloy hot extruded sheet is first subjected to 10% to 15% cold rolling deformation, then subjected to 150°C / 1 hour aging treatment to relieve internal stress and improve plasticity, and finally subjected to 1% to 5% cold drawing deformation;
[0010] Step 3: Heat treatment process
[0011] Annealing treatment is performed on the pre-deformed sample at a temperature of 150 to 180°C and a time of 0 to 120 hours and not 0;
[0012] Step 4: Anodizing
[0013] The heat-treated alloy is pickled and electropolished, the electrolyte is 15-20% sulfuric acid, the current density is 1-3A / dm 2 , the temperature is maintained at 0 ~ 20℃.
[0014] As a preferred solution of the method of the present invention, wherein: Er: 0.05%, Zr: 0.1%, Zn: 0.5%.
[0015] As a preferred embodiment of the method of the present invention, the semi-solid forming temperature is 520°C.
[0016] As a preferred embodiment of the method of the present invention, the stirring method adopts mechanical stirring, the stirring speed is 400 revolutions per minute, and the stirring time is 20 minutes.
[0017] As a preferred embodiment of the method of the present invention, the double-stage homogenization process comprises a first stage of heat preservation at 415°C-425°C for 360 min, and a second stage of heat preservation at 515°C-525°C for 1000 min; more preferably, 420°C / 360min+520 / °C×1000min.
[0018] As a preferred solution of the method of the present invention, the cold rolling deformation is 12%, and the cold drawing deformation is 3%.
[0019] As a preferred solution of the method of the present invention, the stabilization annealing process is 165°C / 72h.
[0020] As a preferred embodiment of the method of the present invention, the electrolyte is 18% sulfuric acid, the current density is 2A / dm 2 , the temperature was maintained at 10℃.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The present invention significantly increases the dislocation density inside the alloy through pre-deformation. At the same time, the dislocations interact with the dispersions to hinder the movement of the dislocations during the plastic deformation process, thereby significantly strengthening the alloy.
[0023] (2) The present invention can promote the Al-Mg-Zn phase to replace the β phase that originally precipitated continuously at the grain boundary by performing a suitable stabilization annealing process, thereby greatly improving the corrosion resistance of the alloy.
[0024] (3) The present invention further improves the corrosion resistance of the alloy by performing anodizing treatment on the basis of stabilization annealing, so that the new erbium-containing Al-Mg alloy has excellent mechanical properties while ensuring long-term corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The hardness variation diagrams of Example 1, Example 2, Example 3 and Example 4 of the present invention are shown;
[0026] Figure 2 These are the corrosion depth diagrams of Example 1, Example 2, Example 3, and Example 4 of the present invention. DETAILED DESCRIPTION
[0027] The present invention will be further described in detail below in conjunction with implementation examples, but the present invention is not limited to the following embodiments.
[0028] Embodiment 1:
[0029] The pre-deformation, stabilization annealing and anodizing of the novel erbium-containing aluminum-magnesium alloy include the following steps:
[0030] Step 1: Preparation of Al-Mg alloy sheet
[0031] The chemical composition (wt.%) of an aluminum alloy used in the present invention is: Mg: 5.5%, Zn: 0.5%, Mn: 0.6%, Er: 0.05%, Zr: 0.1%, and the rest is Al. The first step: melt the mixture at 650°C. The second step: quickly cool the alloy to a semi-solid state of 520°C. The third step: stir the aluminum-magnesium alloy in the semi-solid state using a spiral stirrer, with a stirring speed of 400 rpm and a stirring time of 20 minutes. The fourth step: heat the obtained alloy from room temperature to 420°C at a heating rate of 50°C / hour, keep it warm for 360 minutes, continue to heat it to 520°C, keep it warm for 1000 minutes, and then cool it to room temperature with the furnace. The fifth step: heat the alloy to 500°C and keep it warm for 16 hours before starting extrusion, with an extrusion pressure of 103mN, an extrusion speed of 0.6mm / s, and an extrusion ratio of 26.57, and finally obtain a new type of erbium-containing aluminum-magnesium alloy hot extrusion sheet.
[0032] Step 2: Preparation of pre-deformed samples
[0033] The pre-deformation method is a combination of cold rolling and cold drawing. The alloy is first cold rolled by 12%, then aged at 150°C for 1 hour to relieve internal stress and improve plasticity, and finally cold drawn by 3%.
[0034] Step 3: Heat treatment process
[0035] The pre-deformed samples were annealed at 165°C for 72 h.
[0036] Step 4: Anodizing
[0037] The alloy was pickled and electropolished with 18% sulfuric acid as electrolyte and a current density of 2A / dm 2 , the temperature was maintained at 10℃.
[0038] Embodiment 2 (comparative example):
[0039] Step 1: Preparation of Al-Mg alloy sheet
[0040] The chemical composition (wt.%) of an aluminum alloy used in the present invention is: Mg: 5.5%, Zn: 0.5%, Mn: 0.6%, Er: 0.05%, Zr: 0.1%, and the rest is Al. The first step: melt the mixture at 650°C. The second step: quickly cool the alloy to a semi-solid state of 520°C. The third step: use a spiral stirrer to stir the aluminum-magnesium alloy in a semi-solid state, with a stirring speed of 400 rpm and a stirring time of 20 minutes. The fourth step: heat the obtained alloy from room temperature to 420°C at a heating rate of 50°C / hour, keep it warm for 360 minutes, continue to heat to 520°C, keep it warm for 1000 minutes, and then cool it to room temperature with the furnace. The fifth step: heat the alloy to 500°C and keep it warm for 16 hours before starting extrusion, with an extrusion pressure of 103mN, an extrusion speed of 0.6mm / s, and an extrusion ratio of 26.57, and finally obtain a new type of erbium-containing aluminum-magnesium alloy hot extrusion sheet;
[0041] Step 2: Preparation of pre-deformed samples
[0042] Example 2 keeps the original state without pre-deformation process;
[0043] Step 3: Heat treatment process
[0044] Example 2 maintains the original state without undergoing stabilization annealing process.
[0045] Step 4: Anodizing
[0046] Example 2 keeps the original state without anodizing treatment.
[0047] Embodiment 3 (comparative example):
[0048] Step 1: Preparation of Al-Mg alloy sheet
[0049] The chemical composition (wt.%) of an aluminum alloy used in the present invention is: Mg: 5.5%, Zn: 0.5%, Mn: 0.6%, Er: 0.05%, Zr: 0.1%, and the rest is Al. The first step: melt the mixture at 650°C. The second step: quickly cool the alloy to a semi-solid state of 520°C. The third step: stir the aluminum-magnesium alloy in the semi-solid state using a spiral stirrer, with a stirring speed of 400 rpm and a stirring time of 20 minutes. The fourth step: heat the obtained alloy from room temperature to 420°C at a heating rate of 50°C / hour, keep it warm for 360 minutes, continue to heat it to 520°C, keep it warm for 1000 minutes, and then cool it to room temperature with the furnace. The fifth step: heat the alloy to 500°C and keep it warm for 16 hours before starting extrusion, with an extrusion pressure of 103mN, an extrusion speed of 0.6mm / s, and an extrusion ratio of 26.57, and finally obtain a new type of erbium-containing aluminum-magnesium alloy hot extrusion sheet.
[0050] Step 2: Preparation of pre-deformed samples
[0051] The pre-deformation method is a combination of cold rolling and cold drawing. The alloy is first cold rolled by 12%, then aged at 150°C for 1 hour to relieve internal stress and improve plasticity, and finally cold drawn by 3%.
[0052] :Step 3: Heat treatment process
[0053] Example 3 maintains the state after pre-deformation and does not perform stabilization annealing process treatment.
[0054] Step 4: Anodizing
[0055] Example 3 maintains the state after pre-deformation and does not perform anodizing treatment.
[0056] Embodiment 4 (comparative example):
[0057] The chemical composition (wt.%) of an aluminum alloy used in the present invention is: Mg: 5.5%, Zn: 0.5%, Mn: 0.6%, Er: 0.05%, Zr: 0.1%, and the rest is Al. The first step: melt the mixture at 650°C. The second step: quickly cool the alloy to a semi-solid state of 520°C. The third step: stir the aluminum-magnesium alloy in the semi-solid state using a spiral stirrer, with a stirring speed of 400 rpm and a stirring time of 20 minutes. The fourth step: heat the obtained alloy from room temperature to 420°C at a heating rate of 50°C / hour, keep it warm for 360 minutes, continue to heat it to 520°C, keep it warm for 1000 minutes, and then cool it to room temperature with the furnace. The fifth step: heat the alloy to 500°C and keep it warm for 16 hours before starting extrusion, with an extrusion pressure of 103mN, an extrusion speed of 0.6mm / s, and an extrusion ratio of 26.57, and finally obtain a new type of erbium-containing aluminum-magnesium alloy hot extrusion sheet.
[0058] Step 2: Preparation of pre-deformed samples
[0059] The pre-deformation method is a combination of cold rolling and cold drawing. The alloy is first cold rolled by 12%, then aged at 150°C for 1 hour to relieve internal stress and improve plasticity, and finally cold drawn by 3%.
[0060] Step 3: Heat treatment process
[0061] The pre-deformed samples were annealed at 165°C for 72 h.
[0062] Step 4: Anodizing
[0063] Example 4 maintains the state after stabilization annealing and does not perform anodizing treatment.
[0064] Table 1 shows the mechanical properties of Example 1, Example 2, Example 3 and Example 4. Compared with Example 1, Example 2 maintains the original state after hot extrusion, and its tensile strength is 355.5MPa, yield strength is 168.5MPa, and elongation is 23%; Example 3 only undergoes pre-deformation process, and its tensile strength is 366MPa, yield strength is 267MPa, and elongation is 17.5%. Due to the increase in deformation, the internal dislocation density of the alloy in Example 3 increases significantly. It can be seen from Table 1 that the yield strength of the alloy increases significantly, which is 58% higher than that of the sample without pre-deformation, but the elongation is also reduced. Example 4 combines pre-deformation with stabilization annealing process, and its corresponding yield strength is 243MPa, tensile strength is 361MPa, and elongation is 21.5%. Compared with Example 3, the mechanical properties of Example 1 are slightly reduced, but compared with Example 2, its mechanical properties are still greatly improved.
[0065] Table 2 shows the intergranular corrosion performance of Example 1, Example 2, Example 3 and Example 4. The intergranular corrosion experiment complies with the ASTM G67 standard to quantitatively evaluate the intergranular corrosion phenomenon, and uses the nitric acid weight loss method as the main analysis method. First, the size of the sample is measured and its surface area is calculated. Then, the specimen is immersed in a pre-prepared 200 ml 5% hot alkaline solution, maintaining the solution temperature at 80°C, and pretreated for one minute. After the pretreatment is completed, rinse with clean water. Subsequently, the sample is completely immersed in concentrated nitric acid with a concentration of 64-69wt.% at room temperature for 30 seconds. After rinsing again, dry naturally at room temperature, and use a balance to weigh the mass of the sample at this time. In a constant temperature water bath device, 120 ml of 64-69wt.% concentrated nitric acid is configured, and the water bath temperature is set to 30±0.1°C. After the sample is left to stand for 24 hours under this condition, it is taken out and fully rinsed with deionized water. After it is naturally air-dried to a constant weight state, the final mass measurement is performed. Based on the mass difference of the sample before and after treatment, the intergranular corrosion weight loss per unit area is calculated in mg / cm 2 .
[0066] According to ASTM G67, if the NAMLT value is less than or equal to 15 mg / cm 2 , the alloy is judged to be resistant to IGC. When NAMLT is greater than or equal to 25 mg / cm 2 When the material is 1.5 mg / cm2, it can be seen that the weight loss value of Example 2 is 16.6 mg / cm2. 2 At this time, the alloy is in a sensitive state and has poor corrosion resistance. The weight loss value of Example 3, which has only undergone pre-deformation, reached 28.7 mg / cm 2 The weight loss value increased significantly, and the corrosion resistance deteriorated. The weight loss value of Example 4, which was combined with pre-deformation and stabilization annealing, was 11.6 mg / cm 2 At this time, the alloy is in an insensitive state and has good corrosion resistance. After pre-deformation, stabilization annealing and anodizing treatment, the weight loss value of Example 1 dropped significantly to 3.3 mg / cm 2 , showing the best corrosion resistance.
[0067] In order to further compare the IGC resistance, the cross-section of the corroded sample was observed using an optical microscope. Table 2 shows the corrosion depth of different samples after intergranular corrosion. It can be seen that the corrosion depth corresponds to the result of the weight loss value. Among them, the corrosion depth of Example 3 reached 79.9μm, showing the worst corrosion resistance, and the corrosion depth of Example 1 was 9.7μm, with the best corrosion resistance.
[0068] The above-described embodiments are preferred implementation modes of the present invention, but the present invention is not limited to the above-described implementation modes. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.
[0069] Table 1 Mechanical properties of alloys
[0070] alloy Tensile strength(MPa) Yield strength (MPa) Elongation(%) Hardness (HV) Example 1 363 248 20 115 Example 2 355.5 168.5 23 88 Example 3 366 267 17.5 118 Example 4 361 243 21.5 103
[0071] Table 2 Intergranular corrosion performance of alloys
[0072] alloy <![CDATA[Weight loss (mg / cm 2 )]]> Corrosion depth (μm) Example 1 3.3 9.7 Example 2 16.6 25.3 Example 3 28.7 79.9 Example 4 11.6 15.2
Claims
1. A method for improving the mechanical properties and corrosion resistance of erbium-containing Al-Mg alloy, characterized in that: The following steps are involved: (1) Preparation of Al-Mg alloy sheets The chemical composition (wt.%) of the aluminum alloy is: Mg: 5.2-6.2%, Zn: 0.3-0.8%, Mn: 0.5-0.7%, Er: 0.04-0.3%, Zr: 0.05-0.15%, Fe<0.3%, Si<0.2%, and the rest is Al; the aluminum-magnesium alloy sheet is prepared by semi-solid forming technology; the first step: melt the mixture at 600℃~700℃; the second step: quickly cool the alloy to a semi-solid state of 480-580℃; the third step: use a spiral The stirrer stirs the aluminum-magnesium alloy in a semi-solid state at a stirring speed of 300 to 500 rpm for 10 to 30 minutes; the fourth step: subjecting the alloy to a double-stage homogenization annealing of (415 to 425)°C × 360min + (515 to 525)°C × 1000min; the fifth step: heating the alloy to 500°C and keeping it warm for 16 hours before extruding, with an extrusion pressure of 103mN, an extrusion speed of 0.6mm / s, and an extrusion ratio of 26.57, to finally obtain a new type of erbium-containing aluminum-magnesium alloy hot extrusion sheet; (2) Preparation of pre-deformed samples The pre-deformation method is a combination of cold rolling and cold drawing. First, a 10% to 15% cold rolling deformation is performed, followed by an aging treatment at 150°C / 1 hour, and finally a 1% to 5% cold drawing deformation is performed; (3) Heat treatment process (4) performing an annealing treatment on the pre-deformed sample at a temperature of 150 to 180° C. for a time of 0 to 120 h and not 0; (5) Anodizing The heat-treated alloy is pickled and electropolished, the electrolyte is 15-20% sulfuric acid, the current density is 1-3A / dm 2 , the temperature is maintained at 0 ~ 20℃.
2. The method according to claim 1, a method for improving the mechanical properties and corrosion resistance of a novel erbium-containing Al-Mg alloy, characterized in that: In the step (1), the mass percentage content of Er in the aluminum alloy is 0.05%, Zr: 0.1%, and Zn: 0.5%.
3. The method according to claim 1, a method for improving the mechanical properties and corrosion resistance of a novel erbium-containing Al-Mg alloy, characterized in that: In the step (1), the stirring speed is 400 rpm and the stirring time is 20 minutes.
4. The method according to claim 1, a method for improving the mechanical properties and corrosion resistance of a novel erbium-containing Al-Mg alloy, characterized in that: In the step (1), the double-stage homogenization process is carried out with the first stage being kept at 415°C to 425°C for 360 minutes, and the second stage being kept at 515°C to 525°C for 1000 minutes.
5. The method according to claim 1, characterized in that In the step (1), the double-stage homogenization process is 420°C / 360min+520 / °C×1000min.
6. The method according to claim 1, characterized in that The cold rolling deformation is 12% and the cold drawing deformation is 3%.
7. The method according to claim 1, characterized in that The stabilization annealing process is 165°C / 72h.
8. The method according to claim 1, characterized in that The electrolyte is 18% sulfuric acid and the current density is 2A / dm 2 , the temperature was maintained at 10℃.
Citation Information
Patent Citations
Thermal treatment process for erbium-containing aluminum-magnesium-manganese wrought aluminium alloy
CN101403080A
Al-Mg-Mn-Er-Zr alloy rolling and stabilizing annealing process
CN105861892A
Al-Mg-Mn-Sc-Zr aluminum alloy and method for preparing aluminum alloy plate
CN111621680A
Method for improving intergranular corrosion resistance of super austenitic stainless steel
CN113881830A
Long-term corrosion-resistant aluminum alloy cold-rolled plate and preparation method thereof
CN116970850A